Improving Students’ Communication Skills: A Literature Review on the Effectiveness of Teams Games Tournament-Based Learning - Anggriawan Eka Wardhana; Muhammad Hanif; Ibadullah Malawi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Communication skills are one of the key competencies needed in the workplace, but educational institutions have not been able to optimally develop these skills in students. The use of conventional learning methods that are still dominant results in low student participation and interaction in the learning process. This study aims to analyze and evaluate the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in improving students' communication skills. This study uses a qualitative approach with a literature review design. The research subjects consisted of 25 scientific articles relevant to the TGT model and communication skills, which were selected based on inclusion criteria. The data collection method used documentation techniques with instruments in the form of document analysis sheets compiled based on communication skills indicators. Instrument validity was carried out through content validity testing and source triangulation. Data analysis was carried out using descriptive qualitative analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of the TGT model significantly improved students' communication skills, as indicated by increased participation, interaction, and students' ability to convey ideas. This study concludes that the TGT model is effective in improving students' communication skills. The implications of this study indicate that the application of innovative and interactive learning models needs to be optimized to improve the quality of learning.